Mycobacterium avium Subsp. hominissuis Interactions with Macrophage Killing Mechanisms - Norah Abukhalid (MDPI AG, 2021)
Non-tuberculosis mycobacteria (NTM) are ubiquitously found throughout the environment. NTM can cause respiratory infections in individuals with underlying lung conditions when inhaled, or systemic infections when ingested by patients with impaired immune systems. Current therapies can be ineffective at treating NTM respiratory infections, even after a long course or with multidrug treatment regimens. NTM, such as Mycobacterium avium subspecies hominissuis (M. avium), is an opportunistic pathogen that shares environments with ubiquitous free-living amoeba and other environmental hosts, possibly their evolutionary hosts. It is highly likely that interactions between M. avium and free-living amoeba have provided selective pressure on the bacteria to acquire survival mechanisms, which are also used against predation by macrophages. In macrophages, M. avium resides inside phagosomes and has been shown to exit it to infect other cells. M. avium’s adaptation to the hostile intra-phagosomal environment is due to many virulence mechanisms. M. avium is able to switch the phenotype of the macrophage to be anti-inflammatory (M2). Here, we have focused on and discussed the bacterial defense mechanisms associated with the intra-phagosome phase of infection. M. avium possesses a plethora of antioxidant enzymes, including the superoxide dismutases, catalase and alkyl hydroperoxide reductase. When these defenses fail or are overtaken by robust oxidative burst, many other enzymes exist to repair damage incurred on M. avium proteins, including thioredoxin/thioredoxin reductase. Finally, M. avium has several oxidant sensors that induce transcription of antioxidant enzymes, oxidation repair enzymes and biofilm- promoting genes. These expressions induce physiological changes that allow M. avium to survive in the face of leukocyte-generated oxidative stress. We will discuss the strategies used by M. avium to infect human macrophages that evolved during its evolution from free-living amoeba. The more insight we gain about M. avium’s mode of pathogenicity, the more targets we can have to direct new anti-virulence therapies toward.